Does ondansetron attenuate amphetamine-induced behaviour in human volunteers? - Silverstone, P; Johnson, B; Cowen, P (1992)
The effect of the 5-HT3 receptor antagonist, ondansetron, on the decrease in hunger produced by amphetamine was assessed in nine male volunteers using a double-blind cross-over design. Amphetamine (15 mg orally) produced a significant decrease in self-ratings of hunger 2.5 h after administration. This effect was significantly attenuated by pre-treatment with ondansetron (12 mg orally over 24 h). These findings in humans are consistent with data from animal studies suggesting that ondansetron can attenuate certain catecholamins-mediated behaviours produced by amphetamine. However, explanations founded on pharmacokinetic factors cannot be presently excluded.